Dental pulp stem cell-derived intracellular vesicles prevent orthodontic relapse by inhibiting PI3K/Akt/NF-κB-mediated osteoclast activity - Boyuan Peng; Ziwei Li; Yong Cheng; Henghua Jiang; Qingsong Ye; Guangli Han (Stem Cell Research & Therapy)
Abstract Background Orthodontic relapse, the undesired deviation of teeth from their corrected positions, remains a significant challenge in clinical orthodontics. Incomplete periodontal bone remodeling has been identified as a key factor in this process. Despite decades of research, currently there are no effective strategies to prevent relapse. Methods We isolated and identified dental pulp stem cell-derived intracellular vesicles (DPSC-IV) from human dental pulp tissue. To investigate its effect, DPSC-IV was added to osteoblast or osteoclast differentiation medium. During the orthodontic retention period, DPSC-IV was administrated to rats by subgingival injection. Relapse distance and relapse rate were calculated to evaluate DPSC-IV’s ability to prevent relapse. Additionally, Western blot analysis were used to examine DPSC-IV’s inhibitory effect on osteoclast differentiation. Results DPSC-IV significantly promoted osteoblast differentiation and inhibited osteoclast differentiation. Application of DPSC-IV during retention resulted in a significant reduction in both relapse distance and relapse rate, with improved periodontal structure and decreased osteoclast activity. This effect was mediated by the PI3K/Akt/NF-κB signaling pathway and could be reversed by the PI3K activator insulin-like growth factor-1 (IGF-1). Conclusion This study highlights the potential of DPSC-IV as a novel preventive approach against orthodontic relapse, offering a novel strategy for maintaining long-term orthodontic stability. Graphical Abstract